2000
DOI: 10.1067/mhn.2000.102120
|View full text |Cite
|
Sign up to set email alerts
|

Midline radiofrequency tissue reduction of the palate for bothersome snoring and sleep‐disordered breathing: A clinical trial

Abstract: This study is a prospective, nonrandomized clinical trial initiated to assess the safety and efficacy of radiofrequency tissue reduction of the palate for the treatment of bothersome snoring and sleep-disordered breathing. Twelve healthy volunteers with socially disruptive snoring underwent a baseline polysomnogram along with a battery of visual analog scales (VASs) to measure daytime sleepiness, snoring level, pain, and disturbances of speech and swallowing. After radiofrequency tissue reduction of the palate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
5

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 18 publications
3
43
0
5
Order By: Relevance
“…Only four of the studies reported the duration of snoring before the treatment decision 12, 14–16. The obstruction site was assessed clinically (with or without endoscopy) in 27 studies,7, 12–36 with the use of cephalometry in four,7, 12, 13, 22 and with sleep endoscopy in three studies 15, 20, 30…”
Section: Resultsmentioning
confidence: 99%
“…Only four of the studies reported the duration of snoring before the treatment decision 12, 14–16. The obstruction site was assessed clinically (with or without endoscopy) in 27 studies,7, 12–36 with the use of cephalometry in four,7, 12, 13, 22 and with sleep endoscopy in three studies 15, 20, 30…”
Section: Resultsmentioning
confidence: 99%
“…It was rst established for the treatment of turbinate hypertrophy and was proven to be safe and effective (16,17). Concerning the treatment of sleep disorders, temperature-controlled R F VTR was used in the treatment of velopharyngeal obstruction and it was demonstrated that suf cient reduction in disruptive snoring could be achieved using this minimally invasive technique (18,19). Powell et al (20) adapted temperature-controlled R F VTR for the treatment of tongue base hypertrophy in sleep-disordered breathing (SD B).…”
Section: Introductionmentioning
confidence: 99%
“…It is less invasive than thermal cautery because it is a form of``electrosurgery'' in which current¯ow denatured submucosal tissue. However, it is not easy to control the tissue depth affected by the radiofrequency, so that postoperatively mucosal ulceration may occur [12].…”
Section: Discussionmentioning
confidence: 99%